2023
DOI: 10.1038/s41588-022-01276-9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive multi-omic profiling of somatic mutations in malformations of cortical development

Abstract: Malformations of cortical development (MCD) are neurological conditions displaying focal disruption of cortical architecture and cellular organization arising during embryogenesis, largely from somatic mosaic mutations, and causing intractable epilepsy. Identifying the genetic causes of MCD has been a challenge, as mutations remain at low allelic fractions in brain tissue resected to treat condition-related epilepsy. Here, we report a genetic landscape from 283 brain resections, identifying 69 mutated genes th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…The data obtained here make it the GluN2C-containing NMDAR a possible target in FCD type II caused by somatic variants of the mTOR pathway, as also previously suggested for autosomal dominant TSC (Gataullina et al, 2022; Lozovaya et al, 2014). The importance of GluN2C in the pathogenesis of FCD might even expand beyond the spectrum of mTORopathies, as very recently suggested by the detection of a likely pathogenic, somatic GRIN2C variant in a patient with FCD type I (Chung et al, 2023). Our results also indicated that the GluN2C anomalies observed in our model of FCD followed the same developmental pattern as for Tsc +/- mice, suggesting the existence of a critical time window for GluN2C-mediated pathomechanisms and for related rescue strategies.…”
Section: Discussionmentioning
confidence: 91%
“…The data obtained here make it the GluN2C-containing NMDAR a possible target in FCD type II caused by somatic variants of the mTOR pathway, as also previously suggested for autosomal dominant TSC (Gataullina et al, 2022; Lozovaya et al, 2014). The importance of GluN2C in the pathogenesis of FCD might even expand beyond the spectrum of mTORopathies, as very recently suggested by the detection of a likely pathogenic, somatic GRIN2C variant in a patient with FCD type I (Chung et al, 2023). Our results also indicated that the GluN2C anomalies observed in our model of FCD followed the same developmental pattern as for Tsc +/- mice, suggesting the existence of a critical time window for GluN2C-mediated pathomechanisms and for related rescue strategies.…”
Section: Discussionmentioning
confidence: 91%
“…The striking resemblance of the phenotypes observed in cortical CasTcKOs and patients with cobblestone lissencephaly, in addition to the molecular epistasis experiments suggesting that Cas proteins act downstream of Dag1 and β1-Integrin in radial glial cells to maintain basement membrane integrity, pinpoint cytoplasmic effectors of adhesion signaling as possible contributing factors to the etiology of these neurodevelopmental disorders. A recent study revealed that several genes involved in regulating cell-matrix adhesion and IAC assembly are somatically mutated in patients with Focal Cortical Dysplasia [161]. Patients with FCD type I show disruptions of the cortical laminar structure that parallel those observed in Type II lissencephaly, but as the name implies, these dysplasia are more focal in nature, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the "protected" sites are regions of the genome that are less likely to undergo genetic changes. While it is noticing that these regions might be more effectively repaired when damage occurs, or they might be less exposed to factors that cause DNA damage, scientists have not identified the locations of these regions clearly and understand the molecular basis of how these changes in their studies [4,17,18].…”
Section: Advancement In Technologies and Current Challenges To Study ...mentioning
confidence: 99%